Association of varicella zoster virus load in the aqueous humor with clinical manifestations of anterior uveitis in herpes zoster ophthalmicus and zoster sine herpete. Issue 4 (1st February 2008) - Kido, S; Sugita, S; Horie, S; Miyanaga, M; Miyata, K; Shimizu, N; Morio, T; Mochizuki, M
Abstract : Aim: To investigative whether clinical manifestations of anterior uveitis are associated with the viral load of varicella zoster virus (VZV) in the aqueous humor in patients with herpes zoster ophthalmicus (HZO) and zoster sine herpete (ZSH). Methods: After informed consent was given, an aliquot of aqueous humor was collected from patients with VZV anterior uveitis (n = 8). Genomic DNA of the human herpes viruses was measured in the aqueous humor by two PCR assays: a qualitative multiplex PCR and a quantitative real-time PCR. Results: All patients had unilateral acute anterior uveitis with high intraocular pressure, mutton fat keratic precipitates with some pigmentation, and trabecular meshwork pigmentation. Multiplex PCR demonstrated VZV genomic DNA in all of the samples, but not in other human herpes virus samples (human simplex virus types 1 and 2, Epstein–Barr virus, cytomegalovirus and human herpes virus types 6, 7 and 8). Real-time PCR revealed a high copy number of VZV DNA in the aqueous humor. After the initial onset of anterior uveitis, iris atrophy and distorted pupil with paralytic mydriasis developed. The intensity of iris atrophy and pupil distortion, but not ocular hypertension, correlated with the viral load of VZV in the aqueous humor. Conclusion: VZV viral load in the aqueous humor correlated significantly with damage to the iris (iris atrophy and pupil distortion) in patients with HZO and ZSH.